SAFETY AND SECURITY OF SEVESO SITES: STEPPING TOWARDS RESEARCH SYNERGIES AND AN INTEGRATED FRAMEWORK - Cozzani, Valerio (Journal of Integrated Security and Safety Science, 2017)
there is no abstract, this is an opinion paper